Patient-specific iPSC-derived cardiomyocytes reveal abnormal regulation of FGF16 in a familial atrial septal defect. Issue 3 (6th May 2021) - Ye, Lingqun; Yu, You; Zhao, Zhen-Ao; Zhao, Dandan; Ni, Xuan; Wang, Yong; Fang, Xing; Yu, Miao; Wang, Yongming; Tang, Jun-Ming; Chen, Ying; Shen, Zhenya; et al.
Abstract: Aims: Congenital heart disease (CHD) frequently occurs in newborns due to abnormal formation of the heart or major blood vessels. Mutations in the GATA4 gene, which encodes GATA binding protein 4, are responsible for atrial septal defect (ASD), a common CHD. This study aims to gain insights into the molecular mechanisms of CHD using human-induced pluripotent stem cells (iPSCs) from a family cohort with ASD. Methods and results: Patient-specific iPSCs possess the same genetic information as the donor and can differentiate into various cell types from all three germ layers in vitro, thus presenting a promising approach for disease modelling and molecular mechanism research. Here, we generated a patient-specific iPSC line (iPSC-G4 T280M ) from a family cohort carrying a hereditary ASD mutation in GATA4 gene (T280M), as well as a human embryonic stem cell line (ESC-G4 T280M ) carrying the isogenic T280M mutation using the CRISPR/Cas9 genome editing method. The GATA4-mutant iPSCs and ESCs were then differentiated into cardiomyocytes (CMs) to model GATA4 mutation-associated ASD. We observed an obvious defect in cell proliferation in cardiomyocytes derived from both GATA4 T280M -mutant iPSCs (iPSC-G4 T280M -CMs) and ESCs (ESC-G4 T280M -CMs), while the impaired proliferation ability of iPSC-G4 T280M -CMs could be restored by gene correction. Integrated analysis of RNA-Seq and ChIP-Seq data indicated that FGF16 is a direct target of wild-type GATA4. However, the T280M mutation obstructed GATA4 occupancy at the FGF16 promoter region, leading to impaired activation of FGF16 transcription. Overexpression of FGF16 in GATA4-mutant cardiomyocytes rescued the cell proliferation defect. The direct relationship between GATA4 T280M and ASD was demonstrated in a human iPSC model for the first time. Conclusions: In summary, our study revealed the molecular mechanism of the GATA4 T280M mutation in ASD. Understanding the roles of the GATA4-FGF16 axis in iPSC-CMs will shed light on heart development and provide novel insights for the treatment of ASD and other CHD disorders. Graphical Abstract: